Supervision of Secondary School Education in Federal Capital Territory, Abuja: Problems and the Way Forward - Jacob, Ogunode Niyi; Richard, Ugbome Nnamdi (Research Parks Publishing LLC, 2021)
Supervision of secondary school education is plagued with many problems in Nigeria especially in Federal Capital Territory, Abuja. This article discusses the problems preventing effective supervision of secondary school education in Federal Capital Territory, Abuja. Secondary data sourced from print materials and online publications by recognized institutions and individual authors were used in the article. There are many challenges preventing effective supervision of secondary school education in FCT. Prominent amongst the problems include: inadequate funding, inadequate transportation facilities, distance, inadequate supervisors, insecurity, and shortage of supervision materials, poor capacity development programmes and Corruption. To ensure effective supervision of secondary school education in FCT, the article recommended the following: increased funding for secondary school, provision of adequate transport facilities, employment of more professional supervisors, adequate provision of supervision materials, training and retraining programmes for supervisors, provision of adequate security for supervisors on official functions and eradicating all forms of corruption in the ministry of education so as to end diversion of funds meant for supervision.